PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI E-COMMERCE DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Sobirin, Lisda Apriliani; Choeriyah, Putri Utami (Collegium Studiosum Journal, 2024)
Legal protection for consumers in e-commerce transactions is crucial for the development of the community's economy. E-commerce transactions are fundamentally the same as conventional transactions, with the primary difference being the medium used. When business actors and consumers enter into an agreement, both parties are bound and have rights and obligations that must be fulfilled. This writing addresses the issue of how legal protection for consumers in e-commerce transactions is reviewed from the Consumer Protection Law and the legal relationship between parties in e-commerce transactions. The method used in this research is normative juridical research. First, consumer protection is regulated in Law No. 8 of 1999 (UUPK). The objectives of the UUPK include increasing awareness, dignity, and honor of consumers, empowering consumers, and creating a consumer protection system that guarantees legal certainty and information transparency. Second, the parties involved in electronic buying and selling transactions include sellers, buyers, banks, and internet service providers. In sales contracts, the parties have different rights and obligations.